(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
One of the important issues of the "School" social institute is also the creation of favorable psychological and pedagogical conditions for the organization of the effective learning process of left-handed students. This is especially important in the first grade, when a left-handed child enters school and faces a number of inconveniences, because the teaching methods and resources are mainly adapted to the educational conditions of right-handed children. In this process, the role of the teacher is especially important, who must create favorable conditions for the smooth organization of the left-handed child’s adaptation and learning process at school. Currently, a number of methods have been created, which are aimed at improving the educational conditions of left-handed students in accordance with their needs, and their mastery by the teacher enables effective adaptation of left-handed children in school.